Evolution of Indian Banking System and SWOT Analysis of PNB and HDFC - Kumar, Sundeep (Journal of Commerce and Trade, 2016)
For the past three decades India's banking system has several outstanding achievements to its credit. The most striking is its extensive reach. It is no longer confined to only metropolitans or cosmopolitans in India. In fact, Indian banking system has reached even to the remote corners of the country. This is one of the main reasons of India's growth process. The government's regular policy for Indian bank since 1969 has paid rich dividends with the nationalization of 14 major private banks of India. Long time ago; an account holder had to wait for hours at the bank counters for getting a draft or for withdrawing his own money. Today, he has a choice. Gone are days when the most efficient bank transferred money from one branch to other in two days. Now it is simple as instant messaging or dials a pizza. Money has become the order of the day. The need to become highly customer focused has forced the slow-moving public sector banks to adopt a fast track approach. The unleashing of products and services through the net has galvanized players at all levels of the banking and financial institutions market grid to look anew at their existing portfolio offering. These suggestions may contradict to the development policy of the banks. But, these are presented here only after a high voltage SWOT Analysis.